A IMPLEMENTASI PROTEKSI JQUERY AJAX DENGAN PROTEKSI SESION PADA PENGEMBANGAN SISTEM INFORMASI MANAJEMEN KULIAH KERJANYATA DI UNIVERSITAS MUHAMMADIYAH BENGKULU - Uspandi, Engki Trio; Witriyono, Harry (UNIVED Press, 2021)
Websites as a medium for delivering information play a very important role in the digital information era. In carrying out its activities, LP2M utilizes KKN registration application software for processing KKN data. The system that is running at this time has several problems, namely that students have to queue to register with LP2M by filling in the Student Identification Number (NPM) form and their name as username and password. However, by focusing more on discussing the use of AJAX technology on website pages and its impact on the access speed (load time) of a website page, especially in the function section of the AJAX engine, to be able to know and study the use of the functions in JavaScript, it is wrong the only one is the XMLHttpRequest function. The protection system is a transfer and communication process that is carried out asynchronously by client and server computers, the website pages displayed will be more interactive and faster for website page visitors to load.